CONOCIMIENTO Y ACTITUD SOBRE PARTO HUMANIZADO Y SU RELACION CON LOS INTERNOS DEL HOSPITAL SAN JOSÉ, FEBRERO–JUNIO 2019 - HUAMAN CALDERÓN, GUILIANA FABIOLA (2020)
TITLE: "Level of knowledge about humanized birth and its relationship with the attitudes of the inmates of the San José de Chincha Hospital in February - June 2019" OBJECTIVE: To determine the level of knowledge about humanized childbirth and its relationship with the attitudes of the interns of Obstetrics and Medicine at the San José de Chincha Hospital, February-June 2019. METHODOLOGY: A non-experimental, descriptive correlational, quantitative study was conducted with a prospective cross-sectional study, where there was a population consisting of 30 inmates of the San José Hospital in Chincha and the entire population is taken as a sample, because it is a small population. RESULTS: It was obtained as a result based on the characteristics that the obstetrics and medicine inmates have, it was that the average age was 23 to 24 years (63.3%), based on the professional career they were 73.3% medicine and obstetrics with 26.7%, in relation to the house of study with the highest percentage of inmates studying, it was 43.3%, being the San Luis Gonzaga University; a low level of knowledge with 60% and a high level with 10%; an unfavorable attitude was achieved with 60% and unfavorable with 40%. CONCLUSION: the level of knowledge that exists in future professionals about human childbirth is a low level and the attitudes they come to have is unfavorable against humanized childbirth where it was verified by inferential statistics that there is no relationship between the two variables with a result p value of 0.523 (P <0.05). KEY WORDS: Attitude, Level of knowledge, Humanized delivery.